Conditioning regimen intensity and low-dose azacitidine maintenance after allogeneic hematopoietic cell transplantation for acute myeloid leukemia. Issue 12 (14th October 2020) - Ali, Naveed; Tomlinson, Benjamin; Metheny, Leland; Goldstein, Steven C.; Fu, Pingfu; Cao, Shufen; Caimi, Paolo; Patel, Rushang D.; Varela, Juan Carlos; Andrade, Luisa; Balls, Jason W.; Baer, Linda; et al.
Abstract: Azacitidine (AZA) maintenance following allogeneic hematopoietic cell transplantation (HCT) for acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) may reduce relapse risk and improve survival. Given logistic and toxicity-related challenges, identifying subgroups appropriate for this approach is an unmet need. Using data from two centers, we retrospectively compared event-free survival (EFS) and overall survival (OS) of AML and MDS patients who received AZA maintenance ( n = 59) with historic controls ( n = 90). Controls were selected according to the following criteria: no death, relapse, or Grade III–IV acute GVHD for 100 days after transplant. In multivariable analysis, AZA maintenance yielded significantly improved EFS ( p = 0.019) and OS ( p = 0.011). Outcomes differed according to regimen intensity. For reduced-intensity transplant, EFS ( p = 0.004) and OS ( p = 0.004) were significantly improved and equivalent to myeloablative transplant. A significant benefit following myeloablative transplant was not observed. Within the limitation of its retrospective nature, this study suggests that AZA maintenance improves outcomes following reduced-intensity HCT, comparable to myeloablative HCT.